Mitochondrial lipid metabolism in metastatic breast cancer - Bhuban Ruidas (Mitochondrial Communications, 2024)
The significance of mitochondrial lipid metabolism in cancer stemness, survival, and proliferation, particularly in the context of metastasis, has garnered significant attention. Warburg's hypothesis posits that cancer cells primarily rely on aerobic glycolysis for survival due to mitochondrial dysfunction. However, recent evidence has challenged this perspective, emphasizing the direct involvement of mitochondria in cancer's rapid progression. Metabolic rearrangements, a hallmark of metastatic cancer, fulfill heightened energy demands during rapid proliferation, primarily through mitochondrial oxidative phosphorylation and lipid metabolism, even under hypoxic conditions. Moreover, lipid metabolism is elevated throughout the progression of metastatic cancer to meet crucial energy needs. However, the relative importance of mitochondrial lipid metabolism and aerobic glycolysis in highly aggressive cancers remains poorly defined, and further investigation could enhance treatment outcomes in cases of metastatic progression. In this context, a comprehensive understanding of mitochondrial lipid metabolism in metastatic breast cancer patients could potentially lead to significant breakthroughs in improving therapies, especially for triple-negative breast cancer.